Dynamic Analysis of Falling Weight Deflectometer Test Results for Strength of Character of flexible Pavement Layer Moduli - Nega, Ainalem; Al-Qadi, I.; Nikraz, Hamid (ICPT Committee, 2015)
Falling weight deflectometer (FWD) testing has been extensively done in the past to evaluate structural condition based on engineering and also determine the layer moduli of flexible pavements. However, FWD interpretation has increasingly become challenging from time to time because of repeated heavily traffic urban roads, which have experienced multiple traffic shift and milling operations and overlays even if the computed and measured deflection basin has fulfilled the standard to match within a certain tolerable limits. The main objective of this study is to analyze the FWD test results for strength of character of flexible pavement layer moduli in Western Australia so that allowable loads for existing pavement structures can be determine. The BISDEF computer program is used for backcalculation analysis so that different interface pavement layers condition can be handle the multiple loads.FWD deflection data were collected from seven project sites including core data, roadway data and pavement distress information. The results of FWD test of these traffic roads are compared for consistency and assurance of existing pavement structures of Western Australia and then, the conclusions are drawn.